Human resource management practices, affective commitment and perception towards corruption and bribery in Royal Malaysia Police - Lee, Kok Chee (2015)
The main purpose of this study was to investigate the Human Resource Management practices (training and development, career development, salary and benefits and performance appraisal) and the perception towards corruption and bribery in the Royal Malaysian Police. Specifically, it was aim to investigate the mediating effect of affective commitment between Human Resource Management practices (training and development, career development, salary and benefits and performance appraisal) and perception towards corruption and bribery in the Royal Malaysian Police. The motivation for this study was driven by the inconsistent findings in literature concerning the relationships between the Human Resource Management practices (training and development, career development, salary and benefits and performance appraisal) and the perception towards corruption and bribery. Accordingly, this study has integrated the Herzberg’s Two Factor Theory to map and position the possible relationships between the variables in the research framework. The study utilises a survey questionnaire which was randomly distributed to 700 Royal Malaysian Police officers and staffs from 5,647 in Penang. Out of 412 returned questionnaires, 386 (55%) were found to be completed and was used in the analysis. Correlation and regression analysis was used to analyse the relationship between the related variables in the study. The results revealed that career development, salary and benefits and affective commitment are positive determinants of perception towards corruption and bribery while career development, salary and benefits and performance appraisal are positive determinants with affective commitment. Moreover, a partial mediating effect of affective commitment on the relationships between Human Resource Management practices and perception towards corruption and bribery was confirmed by the findings. Finally, contributions and limitations of the study as well as suggestions for future research were discussed.